An expert system prototype to determine Osteoporosis / Azliyana Sulaiman - Azliyana, Sulaiman (2002)
By testing bone mineral density levels in high-risk patients, physicians are able to establish a diagnosis of osteoporosis, predict a patient's fijture fracture risk and monitor changes in bone mineral density due to medical problems or therapeutic interventions but the process in detecting osteoporosis are costly. In order to reduce cost and time, this system will use the minimum of the requirement hardware and software. Patient can prevent form using long-term therapy if the can detect the bone mass in their body. This condition is associated with decreased bone mass in some patients.